An Analysis of the Vocational-Educational Problematics for Substantiating Production Specialist Competencies - V. E. Steinberg; L. V. Vakhidova; E. M. Gabitova (Russian State Vocational Pedagogical University, 2019)
Introduction. Today, the system of secondary vocational education (SVE) is faced by a multi-factorial problem: the training of qualified specialists, taking into account approved federal unified standards; the fulfillment of potential employers' requirements, which often do not coincide with these standards; and the determination of rapid responses to continuous changes in labour market conditions, i. e. the requirement for a qualitative human resources upgrade in regional production clusters and holding companies, as well as numerous small enterprises.The aim of the research was to develop a methodology for analysing vocational-educational problematics. The methodology was designed for the differentiation, specification and justification of relevant specialised competencies, which complement universal and general professional competencies documented in educational standards.Methodology and research methods. As a research methodology, a causal approach was used, specifically implemented in the form of a multi-dimensional matrix informing a stage-by-stage analysis, which links the need for qualified personnel (experts, who have necessary competencies) with the pedagogical conditions for their preparation (formation of necessary competencies in students).Results and scientific novelty. We present a recommendation for the organisational and content-based improvement of specialist education in terms of key SVE tasks and factors. This education should be conducted by means of systematic identification and assessment of multi-dimensional regional and sectoral needs for trained personnel, projections of results of monitoring on educational programmes and development of means for the acquisition of the relevant skills. The structure and algorithm of multi-dimensional matrix analysis, providing a stageby-stage presentation of problems found in industrial enterprises concerning specified SVE graduate competencies, are described and visually presented. This also enables to effectively build and timely adjust the learning process of really demanded, competitive experts capable to realise innovative projects, to master and create new equipment, i. e. to keep the successful operation and development of production and economics of a region and a country in general. The logic-semantic model of formation of transprofessional competencies, which integrates technological, informational, legislative and communicative-interprofessional components, is designed. The model consists of eight coordinate axes ("Structure of package tasks", "Significant factors", "Components", "Theoretical bases", "Implementation", "Criteria of formation of competencies", "Result", "Strategic partners") and reflects internal interrelations between all the elements of process of vocational education.Practical significance. The materials of the research and its results complement the theory and practice of vocational education, on the one hand, by new tools for development of federal and other standards, on the other hand, by methodological means of rational choice and justification through the introduction of the specific profile of variable professional competencies into SVE programmes. The authors proposed the methodological and graphic solutions of the problems and the recommendations, which can be used in the organisations of vocational education.